Kewenangan Ajudikasi Badan Pengawas Pemilu (BAWASLU) dan Implementasinya di Daerah - Rosalia, Feni; SIREGAR, ANITA ANDRIANI (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Lampung, 2018)
The implementation of elections and local elections as a form of democracy in our country requires supervision to be clean from fraud and money politics practices as well as election organizing institutions that have integrity so that the quality of elections and regional elections is in accordance with people's expectations. BAWASLU as the Election Supervisory Body in charge of guarding the KPU as the organizer of the General Election, oversees activities ranging from stages, campaigns, voting to the final election results and receiving reports of administrative violations and alleged money politics. However, there is something new in 2017, namely with the emergence of a new authority of BAWASLU as an election supervisory body to resolve administrative violations and disputes related to TSM (Structured, Systematic and Massif) violations that can administratively cancel nominations through an adjudication hearing process, where Bawaslu the role is like a judge, deciding the application written by the applicant in the petitum. Law No.7 of 2017 concerning General Elections contains breakthroughs in strengthening the authority of the Election Supervisory Body (BAWASLU) in enforcing electoral law, in addition to election crimes, the authority to take action and decide administrative violations in the trial mechanism is in the Election Supervisory Body until issuing decisions that are final and binding. Penyelenggaraan Pemilu dan Pilkada sebagai wujud demokrasi di negara kita membutuhkan pengawasan agar bersih dari praktek-praktek kecurangan dan money politics dan juga lembaga penyelenggara Pemilu yang memiliki integritas sehingga terwujudnya Pemilu dan Pilkada yang berkualitas sesuai dengan harapan rakyat. BAWASLU sebagai Badan Pengawas Pemilu yang bertugas mengawal KPU sebagai penyelenggara Pemilu, mengawasi kegiatan mulai dari tahapan, kampanye, pemungutan suara sampai pada hasil akhir Pemilu serta menerima laporan pelanggaran administratif maupun dugaan money politics. Namun, ada yang baru di Tahun 2017 yaitu dengan munculnya kewenangan baru BAWASLU sebagai lembaga pengawas pemilu untuk meyelesaikan pelanggaran administrasi dan sengketa yang terkait dengan pelanggaran TSM (Terstruktur, Sistematis dan Massif) yang secara administratif dapat membatalkan pencalonan melalui proses sidang ajudikasi, dimana Bawaslu itu peran nya layaknya seorang hakim , memutuskan permohonan yang ditulis pemohon didalam petitum nya. Undang-Undang No.7 Tahun 2017 tentang Pemilihan Umum memuat terobosan penguatan kewenangan Badan Pengawas Pemilu (BAWASLU) dalam menegakan hukum pemilu, Selain tindak pidana pemilu, kewenangan menindak dan memutus pelanggaran administrasi dalam mekanisme persidangan ada di Bawaslu hingga mengeluarkan putusan yang bersifat final dan mengikat.